Food Allergy Management at School. (2nd March 2020) - Dupuis, Roxanne; Kinsey, Eliza Whiteman; Spergel, Jonathan M.; Brown‐Whitehorn, Terri; Graves, Amy; Samuelson, Kate; Epstein, Caleb; Mollen, Cynthia; Cannuscio, Carolyn C.
ABSTRACT: BACKGROUND: Approximately 8% of schoolchildren in the United States experience potentially life‐threatening food allergies. They must diligently avoid allergenic foods and have prompt access to epinephrine to treat anaphylaxis. These prevention strategies must be sustained without interruption, posing a range of challenges at school. METHODS: We conducted semi‐structured interviews with 178 participants about their experiences managing food allergies outside the home. Interviews were transcribed and analyzed using an iterative approach in NVivo 10. RESULTS: Participants reported highly varied school experiences across the ecological model. They described the need to be proactive and self‐sufficient to manage food allergies. Whereas food allergy‐related social exclusion was common, participants also described positive peer interactions, including intensive peer engagement and support. They perceived that formal school policies were limited in scope and inconsistently implemented. Prevention‐oriented policies were more common in lower grades than in higher grades. CONCLUSIONS: Poorly defined and implemented policies disrupted students' social and educational experiences at school, families' relationships with school staff, and, ultimately, the safety and wellbeing of students with allergies. Given the high prevalence of food allergies among children, these findings demonstrate the need for multiple layers of support to facilitate safe, socially inclusive food allergy management at schools.